CRITICISM OF DEEP SEA MININGAND THE ISA REGULATORY VOID: THE ROLE OF THE BBNJ AGREEMENT AS A PROTECTION MECHANISM - Dwi Putra, Dimas Raditya (Sekolah Tinggi Ilmu Hukum Awang Long, 2025)
Deep Sea Mining (DSM) in international areas has triggered various controversies due to serious ecological risks and regulatory uncertainty in the International Seabed Authority (ISA). This article aims to examine the legal gaps related to DSM and evaluate the potential of the Biodiversity Beyond National Jurisdiction (BBNJ) Agreement as a temporary protection mechanism until the ISA Mining Code is finalized. The analysis is carried out through a normative approach by reviewing international law of the sea principles such as the “common heritage of mankind,” the precautionary principle, and the ecosystem approach, as well as their relevance in the context of DSM. The study results show that although BBNJ cannot fully replace ISA legally, this agreement offers a significant additional layer of protection for the marine environment through the obligation to conduct environmental impact assessments and the establishment of marine protected areas. This research also reveals conflicts of interest and inequalities in the benefit-sharing mechanism that potentially disadvantage developing countries. In conclusion, BBNJ plays an important role as a complementary instrument that can strengthen DSM oversight, but does not replace the comprehensive regulations required from ISA.